Effects of wind driven rainfalls on soil loss from a Douro vineyard, Portugal - Figueiredo, Tomás de (2020)
In permanent row crops, rainfall interception by canopies in rows varies according to wind direction and this may affect raindrop impact and erosion in the inter-row area. The paper aims at discussing the effects of wind direction during rainfalls on soil loss from vineyard plots with different slope aspect in the Douro Region, Portugal. Long term continuous rainfall records, daily wind direction, and soil loss from 5 plots (32m long x 5n wide), in a 45% slope row‐planted vineyard, with slope aspect from NW to SW, were explored separating events only with water loss (NER, 67 non‐erosive events) from the others (ERO, 100 erosive events), and considering for each event wind direction at peak rainfall intensity. Calm atmosphere prevailed but with lower frequency in ERO (65%) than in NER (72%). Most frequent winds were NW (20%) and S (11%) in ERRO, and SE (12%) and NW (7%) in NER. Wind direction affected the differences between plots in event soil loss (expressed by the CV of the 5 plots soil loss in each event), with a CV 90% for NW winds, 37% for S, and 33% for Calm. NW winds blow parallel to vine rows in some plots and almost perpendicular in the others and this effect was most evident during the larger erosion events when lowest to highest plot soil loss ratio reached 1:50. These results may contribute to better tune the application of conservation measures in Douro vineyards considering plot location and dominant wind direction.